Szlakami Teorii Sprężystości - Nowiński, Jerzy (Engineering Transactions, 1955)
A general historical survey of mechanics of deformable bodies, in which the history of that science is divided into three periods (from Galileo to Navier, from N a vier to the creation of the theory of plasticity and from that date up to the present), is followed by a suggestion of the principal directions in which, in the author's opinion, the science of mechanics of deformable bodies should be developed in Poland. The problems suggested are as follows. (1) Investigation of the principles of mechanics of deformable bodies. (2) Physical problems concerned with solid bodies and the phenomena of deformability.(3) Studies with the object of rendering the ideal model of a solid body more real, by considerations involving the properties of anisotropy, non-homogeneity, non-linearity, etc.(4) Generalization of the theory of torsion and bending of solid beams.(5) Further studies of plates with special consideration of the properties mentioned in (3).(6) Extensive development of the theory of thin-walled structures. (7) Contact problems.(8) The theory of plasticity, rheology and associated problems involving the limit states of equilibrium. (9) Mathematical problems concerning energy methods. (10) Arrangement of other branches of the theory of elasticity. (11) Applications of probability methods. (12) The problem of prestressing. (13) Problems concerning the dynamics of deformable systems, experimental methods and friction.The author's opinion is that the development of the branches of mathematics used in the problems of mechanics of deformable bodies should be encouraged. This concerns, in particular, the theory of finite differences, the Laplace transformation and the Fourier integral, integral equations, tensor calculus etc.